2000
DOI: 10.7589/0090-3558-36.3.450
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Zuclopenthixol Acetate to Decrease Handling Stress in Wapiti

Abstract: Handling stress and capture myopathy are important consequences of intensively managing wildlife species. Over the last 15 yr, the use of long-acting neuroleptic (LAN) drugs in wildlife has increased, and these drugs have become a valuable tool for decreasing capture and handling stress in many species. At this time, reports on the use of these drugs in North American species are limited. The major objective of this study was to evaluate the use of the LAN, zuclopenthixol acetate (Clopixol-Acuphase), to decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Bosson et al 2012;Ponjoan et al 2008). Even though some studies claim that using chemical immobilization reduces capture and handling stress (Montané et al 2002;Read et al 2000), we argue that not using anaesthesia can be an advantage: Our procedure meant that beavers were released immediately back into their familiar surroundings (including lodges and burrows for refuge) without adverse affects from anaesthesia and/or surgery. Tagged beavers were quite often observed swimming or foraging shortly after release (F. Rosell, personal communication), which confirms our assumption.…”
Section: Reduced Activity Level (Mean Odba)mentioning
confidence: 99%
“…Bosson et al 2012;Ponjoan et al 2008). Even though some studies claim that using chemical immobilization reduces capture and handling stress (Montané et al 2002;Read et al 2000), we argue that not using anaesthesia can be an advantage: Our procedure meant that beavers were released immediately back into their familiar surroundings (including lodges and burrows for refuge) without adverse affects from anaesthesia and/or surgery. Tagged beavers were quite often observed swimming or foraging shortly after release (F. Rosell, personal communication), which confirms our assumption.…”
Section: Reduced Activity Level (Mean Odba)mentioning
confidence: 99%
“…Behavioural categories are described in Ethogram Table 2 avoid fall-related wounds during capture is to keep the floor of the trap in a non-slippery condition. The use of anaesthesia is typically motivated by stress reduction (Teixeira et al 2007) or to reduce the incidence of capture myopathy (Read et al 2000). However, tranquilizing has not always been shown to improve survival (Letty et al 2000), and one explanation can be the lack of control that can act as a stressor for the animal (Sapolsky 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Objective measures of stress such as heart rate, temperature, and blood parameters were more variable, but tended to suggest less stress in the treated animals than in controls. No side effects of the drug were observed in any of the animals in these studies, given a dose of 1 mg/kg IM [15,17,18], however extrapyramidal signs have been reported to occur early in treatment or at higher doses [4]. In one report [10], apparent extrapyramidal signs were observed in two white-tailed deer, manifesting as continuous self-grooming and facial movements.…”
Section: Use Of Long-acting Neuroleptics In Wildlifementioning
confidence: 99%
“…Several authors have examined both subjective and objective effects of this drug, in attempt to describe its usefulness. Its effects have been recently evaluated in red deer [15], bison [16], Nile lechwe [17], wapiti [18], and white-tailed deer [10], in addition to numerous historical references. It has been used alone [17,18] and in combination with other tranquilizers such as azaperone [10,16] and perphenazine [15].…”
Section: Use Of Long-acting Neuroleptics In Wildlifementioning
confidence: 99%
See 1 more Smart Citation